Cancer bioinformatics: An early precision tool - Manisha Saxena; Manoj Meena; Ajay Kajla; Bajrang Lal (Wolters Kluwer Medknow Publications, 2023)
Oral squamous cell carcinoma (OSCC) constitutes substantial part of head and neck squamous cell carcinoma (HNSCC). Unfortunately, more than 50% of patients with oral cancer display evidence of spread to regional lymph nodes and metastases at the time of diagnosis, and approximately two-thirds of patients have apparent symptoms at presentation, a negative prognostic indicator. Cancer bioinformatics is a critical part of the medicine and the core tool to carry out the investigations of cancer and developing more personalised treatment strategies. This short communication explores contribution of cancer bioinformatics in increasing our understanding of cancer biology, diagnosis, prognosis and treatment.